A Diagnostic Study Using STARD Platform on Liquid-Based Cytology in Cervical Smear and Its Positivity Rate among Females with Abnormal Vaginal Conditions Attending a Tertiary Care Center - Mohd Afzal; Abhishek Sharma; Vikas Tiwari; Jaishree Karnwal Tiwari (Journal of Cytology)
Background: Liquid-based cytology (LBC) is a newer method of preparing cervical cell samples. This technique involves collecting cells in a liquid fixative and preparing and evaluating them. Aim: This study aims to investigate cervical smears prepared using the Ezi-Prep LBC method and analyze the positivity rate for cervical cancer and assess the diagnostic accuracy of LBC in detecting cervical abnormalities among females with abnormal vaginal conditions attending a tertiary care center. Materials and Methods: The present diagnostic study was performed in a tertiary care hospital over a period of 1 year (April 1, 2021–November 30, 2021). A total of 230 women, aged 21–70 years, presented at the gynecology outpatient department for either routine cervical screening or with complaints of vaginal bleeding, discharge, or pelvic pain. Cervical smears were prepared using the Ezi-Prep method and stained with ULTRA-PAP stain. Results: LBC smears are monolayer smears and are without nuclear overlapping with spread over a diameter of 16 mm. Minimum cellular overlapping and crowding were observed in LBC smears. The mean age of the participants was 35.5 ± 5.1 years. The smears were studied by using nine morphological parameters. Conclusion: The majority of the smears were inflammatory smears. A total of 16 cases and three cases were found to be bacterial vaginosis and candidiasis, respectively. In an 8-month study, HSIL was found in two cases, whereas LSIL was found in only one case. The positivity rate was observed to be 0.9% in HSIL cases and 0.4% in LSIL cases, 0.9% ASC-US case, and 0.4% invasive carcinoma case.